A New Interpretation of the ‘External Portico’ of Arin-berd/Erebuni, Armenia - Dan, Roberto (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
This article is devoted to a reconsideration of an unusual structure discovered during the excavation of the fortress of Arin-berd, ancient Erebuni, which is located in the southwestern outskirts of Yerevan, the capital of Armenia. This building, which is connected to the main gate of the fortress, was considered by Konstantin Oganesjan, the main excavator of the site, to be a portico used as a sort of reception facility. This article puts forward a new interpretation of the building, that is inserted in a wider project of re-evaluation of the site.